O processo de construção do ethos no discurso de sujeitos tutores virtuais - Mareco, Raquel Tiemi Masuda (2017)
This research aims to analyze the discursive functioning of ethos construction process of the subject who comments their teaching practices from the virtual tutor social place, passing this analysis through the identification process of this subject with the subjectform, and the materialization of teaching-related stereotypes. It is a work from linguistics field, in the line of research: Text and Discourse Studies, having as theoretical basis the French Discourse Analysis (DA). We discuss issues on the discourse of the subject who works on Distance Education (DE), as a virtual tutor. Our research material consists of 30 interviews with virtual tutors who work in technical, undergraduate, or specialization distance courses in public and private educational institutions in different regions of the country. Based on DA, our methodology begins with the problematization of self-image made by the virtual tutor subject in social-historical emergency conditions of DE discourses. This problematization was synthesized in four questions: a) How does the process of identifying the virtual tutor subject with the subject-form of the FD to which he is affiliated occur?; b) How do stereotypes related to teaching are materialized in the discourse of the subject during the identification process?; c) How is the Other discourse brought in the discursivization of the pedagogical practices mentioned by the virtual tutor subject?; d) What ethé does the subject virtual tutor construct when they discursivize their pedagogical practices?. We selected the interview as an instrument for collecting the material, and transcribed it. From this file reading, we constructed and analyzed a discursive corpus organized in discursive sequences of regularities in the functioning of ethos in this discourse, which required a work of relating to the concepts of ethos (MAINGUENAU, 2008a; 2008b), the stereotype issues (AMOSSY, 1995), and from the process of constitution of the subject by the ideology in the modalities of the unfolding of the discursive subject provided by Pêcheux (1995). Our path of analysis has shown that when the virtual tutor subjects discursivize their teaching practice by reproducing what is proper to DE, they show themselves in a process of identification with the know-how inscribed in the Distance Education Discursive Formation (FDEad) and reproduces it, constructing an ethos of efficient tutor, according to this know-how, and from the necessary silencing of what is proper to the discourse of the face-to-face modality, which only returns in moments of failure in this ritual, in the form of a simulacrum. On the other hand, other tutors were in the process of counter-identification, questioning the know-how of the DE in order to make conflicts appear with the Other of the discourse: the face-toface modality, at this moment the questioning tutor ethos arises, whose subject is discordant to Some know-how of discursive formation. Our corpus has also revealed a subject unidentified with the FDEad, who is affiliated to the Face to face Education Discursive Formation (FDEpr), bringing the FDEad's know-how as a simulacrum, and constructing an ethos of a displaced tutor.